1990
DOI: 10.1044/jshr.3303.440
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Voiceless Fricatives by Normal and Hearing-Impaired Subjects

Abstract: The purpose of this study was to investigate the sufficient perceptual cues used in the recognition of four voiceless fricative consonants [s, f, θ, ∫] followed by the same vowel [i:] in normal-hearing and hearing-impaired adult listeners. Subjects identified the four CV speech tokens in a closed-set response task across a range of presentation levels. Fricative syllables were either produced by a human speaker in the natural stimulus set, or generated by a computer program in the synthetic stimulus set. By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
3
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 22 publications
3
41
3
1
Order By: Relevance
“…Harris ( 1957), for example, concluded that such transitions are important for differentiating /f/ from /th/, but not for identifying /s/ and /sh/. In contrast, both Zeng and Turner ( 1990) and Whalen ( 199 1) have demonstrated a significant contribution of vowel formant transitions to the identification of /s/ by hearing subjects. Zeng and Turner ( 1990), however, found that hearing-impaired subjects could not use these formant transitions, but needed to hear the fricative spectra.…”
Section: Discussionmentioning
confidence: 87%
“…Harris ( 1957), for example, concluded that such transitions are important for differentiating /f/ from /th/, but not for identifying /s/ and /sh/. In contrast, both Zeng and Turner ( 1990) and Whalen ( 199 1) have demonstrated a significant contribution of vowel formant transitions to the identification of /s/ by hearing subjects. Zeng and Turner ( 1990), however, found that hearing-impaired subjects could not use these formant transitions, but needed to hear the fricative spectra.…”
Section: Discussionmentioning
confidence: 87%
“…As a result, patients with hearing impairment may use different acoustic cues in consonant discrimination [37] and hence might show altered patterns of consonant confusions compared with subjects with normal hearing.…”
Section: A Case Studymentioning
confidence: 99%
“…Adult listeners with normal hearing seem to make more use of spectral cues for place of articulation information ͑Heinz and Stevens, 1961;Harris, 1958;Hedrick and Ohde, 1993;Hughes and Halle, 1956;Nittrouer, 1992;Nittrouer and Miller, l997a and 1997b;Nittrouer, 2002;Zeng and Turner, 1990͒, and temporal , 1975;Raphael, 1972;Soli, 1982͒. Hearing-impaired listeners may have difficulty integrating amplitude and spectral cues, and may generally place less weight on formant transitions than listeners with normal hearing ͑Hedrick, 1997; Hedrick and Younger, 2003;Zeng and Turner, 1990͒. In addition, listeners with sloping hearing loss commonly have elevated thresholds, and reduced dynamic range, in regions relevant to fricative perception ͑e.g., Dubno et al, 1982;Owens et al, 1972;Sher and Owens, 1974͒. It is likely, then, that clear speech alternations involving fricative spectra may have different results depending on the listener population.…”
Section: Cues To English Fricative Identity In Different Listener mentioning
confidence: 99%